Secured Transaction Systems and Collateral Registries - International Finance Corporation (Washington, DC, 2015)
The main objective of this toolkit is to provide technical advice and guidance to World Bank Group staff, donor institutions, government officials and other practitioners on the implementation of secured transactions law and institutional reforms in emerging market countries. However, the Toolkit has not been designed to eliminate the need for in-person expert advice for governments that undertake to introduce a secured transactions system. It is necessary to take into account the factors that are unique to each jurisdiction. The content of the Toolkit will guide the reader through the various stages of the project cycle (identification, diagnostic, solution design, implementation, and monitoring and evaluation) involved in the introduction of secured transactions reforms. The recommendations presented in the Toolkit are based on IFC s experience in the secured transactions area, the contributions of a number of experts in this field, existing literature, and reform experience in a number of emerging market countries and the existing best practices in jurisdictions with advanced secured transactions systems. While the Toolkit does not cover all aspects of secured transactions reform, it addresses the most important elements of such reform. The Toolkit does not address secured financing systems involving immovable property as collateral. Chapter one contains a brief discussion of the economic rationale for modern secured transactions systems. Chapter two describes the main elements that a proper diagnostic study of the state of secured transactions in a country should contain. Chapter three provides an overview of project management techniques required to support the full project cycle. One of the most important parts of the Toolkit, chapter four, which deals with the implementation of the reform, includes sections on building consensus for the reform, developing and enacting the necessary laws and regulations, designing and implementing a secured transactions registry, building local awareness and conducting secured transactions training. Chapter five of the Toolkit elaborates in detail the monitoring and evaluation strategy that should be employed following the implementation of the project to assess the effect and impact of reforms. Finally, the toolkit contains a number of annexes that include tools available to develop the different phases of the project as well as technical information.